Breves reflexões sobre as revelações entre o clero e o campesinato a partir da medievalística - Santos, Diego Barros dos (2024)
This study seeks to understand the social relationship between the clergy and the peasantry in the Middle Ages, with emphasis on the social position and justifications of the clergy for their domination, as a feudal lord, over the peasants, seeking to understand how this power structure was maintained. Examining the works: The Three Orders or the Imaginary of Feudalism by Georges Duby; Feudal Society by Marc Bloch; The Civilization of the Medieval West by Jacques Le Goff, I perceive the differences between the living conditions and how the Catholic Church shapes the social, economic and political organization between the 5th and 15th centuries using its power to maintain itself with excellence at the top of the weak pyramid using divine justifications without realizing the existing interdependence.